2015
DOI: 10.7464/ksct.2015.21.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Activity of Allyl Isothiocyanate (AITC) Adsorbed in Oyster Shell on Food-borne Bacteria

Abstract: 주제어 : 소성, 굴, Allyl isothiocyanate (AITC), 항균 Abstract : Oyster shells are a waste product from mariculture that creates a major disposal problem in coastal regions of southeast Korea. To make practical use of unused oyster shells, calcined oyster shell (COS) collected from a local company was allowed to adsorb AITC (allyl isothiocyanate), and then tested the powder's ability to inhibit the growth of some potential food borne disease-causing bacteria. COS powder showed bacteriostatic effect that inhibited cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…It is derived from cruciferous vegetables including Brassica juncea (L.) (Indian mustard), Wasabia jamonica (L.) matsum (wasabi), and Armoracia rusticana (horseradish) [180][181][182]. It has been shown to exert anticancer [183][184][185][186][187][188], anti-microbial [189][190][191], and anti-fungal activities [192][193][194][195], while also protecting against neurological disorders [196,197].…”
Section: Extraction Of Allyl Isothiocyanatementioning
confidence: 99%
“…It is derived from cruciferous vegetables including Brassica juncea (L.) (Indian mustard), Wasabia jamonica (L.) matsum (wasabi), and Armoracia rusticana (horseradish) [180][181][182]. It has been shown to exert anticancer [183][184][185][186][187][188], anti-microbial [189][190][191], and anti-fungal activities [192][193][194][195], while also protecting against neurological disorders [196,197].…”
Section: Extraction Of Allyl Isothiocyanatementioning
confidence: 99%
“…Oyster protein can reduce blood pressure ( Achour et al, 1997 ; Tanaka et al, 2006 ). Moreover, some studies have reported bioactive effects of compounds in oyster shell, including anti-inflammatory, antiosteoporosis, antifibrotic, antimicrobial, and antifungal effects, and lipogenesis inhibition ( Lee et al, 2013 ; Xing et al, 2013 ; Han et al, 2015 ; Latire et al, 2017 ; Tran et al, 2015 ; Feng et al, 2021 ; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%